PERANCANGAN E-SCM BERBASIS WEB PADA INDUSTRI PERTANIAN JAGUNG - Annasia Oktaviana Fauzi (Universitas Muhammadiyah Gresik, 2021)
Supply chain management is the process by which the flow of exchange of raw materials, information and finance occurs between the parties involved. The development of technology requires industry players to be able to optimize SCM with technology. Especially in agriculture. In this case the agricultural industry players can implement information technology through the exchange of information in the supply chain can be developed with E-SCM or electronic supply chain management. E-SCM which will be made with information technology that is often used by the public every day is website based using MySQL database with PHP programming language. It is hoped that the existence of this E-SCM will help the corn farming industry in managing the flow of agricultural SCM information exchange.